Italy as a gateway to Europe for African migration: How to deal with the Doll's House effect?. Issue 4 (7th November 2018) - Brugnoli, Alberto; Matteini, Matteo
Abstract: No physical wall would ever be an effective deterrent when opposed to growing inequalities among people in neighbouring regions. Nevertheless, whether or not governments decide to build physical walls on their borders, walls already often exist around each individual migrant, keeping them secluded like in a Doll's House . This is particularly true when applied to the new stream of African migration to Europe, flowing mainly through Italy. In this paper, we propose a conceptual paradigm to show how the Doll's House is structured for this typical stream of migration and we provide some policy suggestions to deal with it.